The bad and the beautiful [videorecording (DVD)] - Minnelli, Vincente; Douglas, Kirk, 1916-2020-; Turner, Lana, 1921-1995; Pidgeon, Walter, 1897-1984; Grahame, Gloria; Raksin, David (MGM Home Entertainment, 1999)
A Hollywood producer who has risen from poverty to power by using people, money, and sex, finds he needs the help of those he has betrayed.